Inter-Firm technology transfer and performance in international joint venture firms - Sazali Abdul Wahab; Raduan Che Rose; Jegak Uli; Haslinda Abdullah (2010)
The main objective of this paper is to empirically examine the effects of two distinct degrees of technology transfer: degree of tacit and explicit knowledge on two dimensions of performance: corporate and human resource performances. Using the quantitative analytical approach, the theoretical model and hypotheses in this study were tested based on empirical data gathered from 128 joint venture companies registered with the Registrar of Companies of Malaysia (ROC). Data obtained from the survey questionnaires were analyzed using the correlation coefficients and multiple linear regressions. The results revealed that degree of tacit knowledge, as a distinct dimension of degree of technology transfer, has a significant effect on both corporate and human resource performances; where its effect was much stronger on corporate performance. Similarly, degree of explicit knowledge has shown consistent strong significant effects on both corporate and human resource performance; where its effect on human resource performance was found much stronger than corporate performance. The study has bridged the literature gaps in such that it offers empirical evidence on the effects of two distinct degrees of technology transfer: degrees of tacit and explicit knowledge on two dimensions of performance: corporate and human resource performances in IJVs.